PENGARUH DISIPLIN TERHADAP EFEKTIVITAS KERJA APARAT PADA KANTOR DESA UJUNG TANAH, KECAMATAN BOLA, KABUPATEN WAJO - Yusran Yusran; Muhammad Aris; Riska Riska (Jurnal Ilmu Administrasi Negara, 2023)
This study aims to find out how much the influence of discipline on the effectiveness of the work of officials at the Ujung Tanah Village Office, Bola District, Wajo Regency. This type of research used is census research with quantitative associative methods. The data collection techniques used are observation, questionnaires, documentation. The population and sample in this study were all apparatus at the Ujung Tanah village office, Bola District, Wajo Regency. Sampling in this study refers to Sugiono's opinion because the population is small, the sample used is a saturated sample. So that the sample in this study is the entire apparatus at the village office. The results of this study indicate that the influence of discipline on the effectiveness of the work of officers at the Ujung Tanah village office, Bola District, Wajo Regency. With the dimension of discipline, the work effectiveness of the apparatus. From the results of the study showed the results of each dimension with an average reach good category.